Germination temperatures affect the physiological quality of seeds of lettuce cultivars (Bioscience Journal, 2019)
The objective of this study was to evaluate the physiological quality allied to biochemical quality of lettuce seeds by germination and enzymes expression at 20, 25, 30, 35, 40 and 42ºC. Germination speed index and percentage of germination were estimated. Isoenzyme expressions were assessed by alcohol dehydrogenase (ADH), malate dehydrogenase (MDH), catalase (CAT), esterase (EST), pyruvate decarboxylase (PDC) and glutamate oxaloacetate transferase (GOT). The experiment consisted of a completely randomized design in a factorial scheme 4x6, with four cultivars and six different temperatures, with four replications. The highest germination and vigor were observed for cv. ‘Everglades’ at 35°C, which proved that this cultivar is thermotolerant. Catalase can be considered a genetic marker for the identification of thermotolerant lettuce cultivars. Cultivar ‘Everglades’ has potential to be used in lettuce breeding programs aimed at cultivars tolerant to high temperatures during germination.